Contribution to the improvement of management in defense logistics - Ljubojević, Srđan D.; Andrejić, Marko D.; Dragović, Nebojša K. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Introduction Changes in social environment require adequate answers of all organizational systems, including defense systems and their logistic systems. Improvement of management in defense logistics involves good knowledge of management theory and practice, knowledge of the impact of ownership and market on management, knowledge of public and other macroeconomic sectors functioning, broader opening towards environment and the exchange of knowledge, information and lessons learned with international environment. The paper presents theoretical and practical knowledge that is prerequisite for improving the management of defense and the management of defense logistic systems.   Definition and the essence of management   Regarding its complexity and a lack of a comprehensive definition, the concept of management is nowadays considered in three ways: as a skill, as social categories - structure of management, as well as a theory - a scientific discipline. When we aanalyze the phenomenon of management, with respect to the historical aspect of its development, there is a necessity to distinguish between management as a scientific discipline and management practice.   Relation between organizational science and management In theory and practice, management is associated with the achievements of many other scientific fields. One of the areas closest to management is organizational science. Today, in the management theory and organization theory, the prevailing attitudes state that these two areas are non-separable and that they are focused on the explaination of the same phenomenon, with the same desire to improve effectivity and development of different purpose systems. There is no clear boundary between organizational science and management, both from theoretical and practical aspects.   Achievements and shortcomings of organizational schools   As a result of solving problems in real systems, a number of opinions and different organizational schools has developed in practice over time. The dominant schools were empirical, qualitative and quantitative approaches. Without intending to diminish the importance of particular approaches or to favor some of them, the paper briefly shows their characteristics. Current trends indicate that organizational schools will develop in two seemingly opposite, but in fact quite consistent approaches: one that will be more interested in people and the other that will be more interested in numbers (psychological and analytical approach).   Management processes and levels   Most of the management theorists emphasize its four functions: planning, organizing, leading and controlling. At the same time, they all observe the management depending on the problems which have to be solved and the appropriate decisions which have to be made. In this sense, the most frequently differentiated are two basic levels of management: strategic and operational. Operational management maintains the existing system’s cohesion, technological discipline and relations stability among the elements of the system and prevents undue breaking of existing economic and technological entities in the system. Strategic management is a combination of internal and external orientation and the use of social power in the decision-making process. It has the key influence on those actions that have strategic importance for the organization. Strategic and operational management are not strictly separated. Their main and common task is to continually adjust and associate activities and functioning of all functions and elements in the system into a single unit, aimed at performing the tasks necessary for survival and development of a wider system. Ownership forms and management   Power and menagemet instruments have always been in the hands of shareholders. The development of economy and social life in general resulted in delegating management authority and responsibility from shareholders to professional managers. In these conditions, ownership retained the power and control instruments at the highest level. The specific form of relations of ownership and management can be found in the so-called public sector as an institutional system of state economic engagement. Stronger organizational democracy and managers and employees participation are  moving in two directions: greater participation in the ownership and greater participation in decision making. This implies closer and partly equalized interests between important internal stakeholders (owners, managers, employees).   Development of management in public sector   The way in which public administration performs its duties (so-called administrative work) has always been a matter of dispute and the desire for reform. Poor quality of communication between users (citizens) and the administrative system has resulted in distrust, on the one hand, and bureaucratization on the other hand. Due to decentralization of political systems, government subjects at various levels of hierarchy have relationships closer to partnership than to subordination. Partnerships require a redistribution of responsibilities, obligations, and funds and other resources among all stakeholders in the management of the affairs of general - common importance. Hence, the term public administration replaced the term government administration, indicating a wider range of entities involved in policy making and implementation of activities. Traditional administrative approach (Public Administration), assuming the concept of elite democracy, relies on three institutional social categories: the party system, the political leadership and the bureaucracy. Accordingly, the authorities can successfully respond to numerous demands and expectations of citizens only by a standardized and administrative approach, particularly in areas such as education, health, economic and monetary system, defense and others. In accordance with its own peculiarities and historical heritage, every country and every society has approached changes in this domain in different ways, but most of these reforms may include the term New Public Management. The societies that have gone deeply in change seek to improve the New Public Management concept by accepting the principle of Public Value ​​Management.   Management in the defense system   Regarding the public sector width, appropriate management models are different  from segment to segment. One of the most specific segments of public sector is the defense system. Regardless of awareness of management in the defense system of the necessity of increasing the effectiveness and efficiency in management, there are numerous risks that may prevent achievement of these goals. Certain specifics in terms of organizational complexity of military systems, in the sense of freedom and autonomy in decision making, human resource management, way of functioning, etc., make defense management,, in some areas, considerably more complex than this is the case with civil organization systems. If mechanisms established to regulate the system have a demotivating character, the consequences can be very negative. Generally, there are two categories of managers in defense systems: general managers and professional managers. A large problem in the management of defense systems is transparency and measurability of results. Accordingly, management reforms in the defense must be directed to the state (the relevant Ministry) which seeks to achieve the set goals in specific areas, and to service users (citizens) who also want high quality of this public service. The characteristics and the results of the management in defense system logistics are direct indicators and a prism through which the management of the overall system can be viewed and its performance evaluated.   Improving the management of defense logistics   Given the global economic situation, many states are trying to achieve the desired efficiency and effectiveness by improving management in the defense, especially in its logistics, through greater synergy in action, with the least consumption of resources while maintaining or even expanding the system capability („Smart defense” concept, „Pool and share” concept, organizational changes in the field of logistics - the set up Joint Logistic Support Groups, etc.). Understanding and implementing these reforms require a special attitude towards the environment and circumstances in which management decisions are made. Logistical and „nonlogistical” management in the defense needs a broader approach to problems, which will provide them consideration of all the consequences that their decisions can have, not only in the defense, but to all stakeholders, especially end-users of services of the defense system - a society or citizens (civilians and citizens in uniform). Management in the defense system often focuses only on one aspect of the final desired state while ignoring its other aspects or impacts on the wider system, the social environment or the state. In fact, it often tends to minimize the costs of defense, regardless of the implications that arise in the field of defense capabilities and levels of security, particularly „in the long run”. Some of the basic principles of good governance in the defense logistics would be: legality, transparency, responsibility, discipline, cooperation and partnership, continuous improvement and others. As a part of planned and organized work to improve management in defense logistics (analogy applies to the defense system as a whole), special attention should be focused on creating a concept that promotes proper selection, choice, education, training, motivation and development of managers among the most competent, the most educated and the most experienced personnel.   Conclusion   Changes in governance in the public sector, more or less, affect all its segments. Given that the budget allocation for defense is rather high and the defense logistics operations are substantial portion of these funds, changes in management are inevitable in this field. Specific defense activities bring specifics in management, but basic assumptions and requirements from management are the same as in all other areas of public services. The effectiveness, efficiency of subsystems and the defense system as a whole, the broad participation of all stakeholders, measurable results, greater transparency, etc, and even the creation of final values and performances, are the management ideals in the domain of defense. The role of management is reflected in the creation of conditions for pooling and sharing resources and overall capabilities, in defining the focus, priorities and gradation in proper coordination so as to achieve coordinated and homogeneous actions. Contemporary managers in the field of defense must understand the areas of financial management, human resource management, project management, crisis management, etc,, and must have the knowledge and skills of decision making, conflict solving, communication and public relations and public choice in general. The essence of the reforms undertaken in defense logistics is to increase responsibility towards the government (the relevant Ministry) which seeks to achieve the defense objectives, and, on the other hand, to increase responsibility towards logistic product and service users (consumers) who wish to obtain public service and high quality products. The complexity of managerial work and the dynamic changes in the logistic system environment require a new approach to selecting, education, training and career development of managers, constantly keeping up with scientific advances and practical experience in management and constant work on acquiring new knowledge and mastery of management methods, techniques and skills.
Keywords: management in the public sector; management and property; causes of inefficiency; levels of management; management process; organizational schools; public sector; management; defense logistics